Clinical and electrophysiological predictors of device-detected new-onset atrial fibrillation during 3 years after cardiac surgery. Issue 12 (1st July 2021) - Bidar, Elham; Zeemering, Stef; Gilbers, Martijn; Isaacs, Aaron; Verheule, Sander; Zink, Matthias D; Maesen, Bart; Bramer, Sander; Kawczynski, Michal; Van Gelder, Isabelle C; Crijns, Harry J G M; Maessen, Jos G; et al.
Abstract: Aims: Postoperative atrial fibrillation (POAF) after cardiac surgery is an independent predictor of stroke and mortality late after discharge. We aimed to determine the burden and predictors of early (up to 5th postoperative day) and late (after 5th postoperative day) new-onset atrial fibrillation (AF) using implantable loop recorders (ILRs) in patients undergoing open chest cardiac surgery. Methods and results: Seventy-nine patients without a history of AF undergoing cardiac surgery underwent peri-operative high-resolution mapping of electrically induced AF and were followed 36 months after surgery using an ILR (Reveal XT™). Clinical and electrophysiological predictors of late POAF were assessed. POAF occurred in 46 patients (58%), with early POAF detected in 27 (34%) and late POAF in 37 patients (47%). Late POAF episodes were short-lasting (mostly between 2 min and 6 h) and showed a circadian rhythm pattern with a peak of episode initiation during daytime. In POAF patients, electrically induced AF showed more complex propagation patterns than in patients without POAF. Early POAF, right atrial (RA) volume, prolonged PR time, and advanced age were independent predictors of late POAF. Conclusions: Late POAF occurred in 47% of patients without a history of AF. Patients who develop early POAF, with higher age, larger RA, or prolonged PR time have a higher risk of developing late POAF and may benefit from intensified rhythm follow-up after cardiac surgery. Clinicaltrials.gov number: NCT01530750.